Sustainability report disclosure level: evidence from telecommunications companies in indonesia and malaysia - Puteri Alfarisa; Mohammad Nasih; Iman Harymawan; Khairul Anuar Kamarudin (The Indonesian Accounting Review, 2023)
This study investigates the disclosure level of sustainability report in telecommunication industry. This study specifically compares the disclosure level of companies in Indonesia and Malaysia using Global Reporting Initiative format template. The study compares the published reports between 2014 to 2016 periods. The results reveal that the disclosure level of sustainability reporting content for companies in both countries are in the intermediate level. Interestingly, our finding shows that companies in Indonesia disclose more content related to economy category. However, they disclose less on product-responsibility, environmental, and human rights categories compared to Malaysian companies. Furthermore, this study provides the investors an insight on how to monitor the disclosure level of the companies in both countries and highlight the demand of specific content to increase the contribution of the companies on specific sustainability issues.